EKSTRAK LIDAH BUAYA TOPIKAL MEMBERIKAN PENGARUH PADA KONSISTENSI SKAR HIPERTROFIK PASKA LUKA BAKAR - Laila Mainur; Harmayetty Harmayetty; Deni Yasmara (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Post-traumatic burns that already heal, very often happens that an ugly scar in the form of hypertrophic scarring, keloids and are often accompanied by the presence of contractures. Hypertrophic and keloid scar is fibroproliferation abnormalities in the dermis that is unique to humans that may arise as a result of burns. While contractures occur because of the shortening of the pathological scarring that causes deformities and movement disorders such as the limited movement of a body part. cases of burns caused 195,000 deaths/year worldwide, especially in poor and developing countries. This aim of this study was to analyze the effect of topical aloe extract against consistency, height, and pigmentation scarring after burns hypertrophic Poly Plastic Surgeon Dr. Soetomo.Methods: This research was used in the pre-experimental design. The population was all patients with burns and 10 patient samples. It used consecutive sampling. The independent variable was aloe vera topical and the dependent variable was the quality of the hypertrophic scar. Data were collected using the Vancouver Scar Scale and then analyzed using Wilcoxon Signed Ranks and Paired T-Test.Result: The results showed that there was significant effect before and after basting of topical aloe vera on the value of consistency (p=0.005). No significant effect before and after the aloe vera in the pigmentation scores (p=0.317) and height. There was a difference significant hypertrophic scar consistency before and after aloe vera extract. No differences in height and pigmentation significant hypertrophic scars before and after extract of aloe vera extract topical effect on the consistency, but not in height and pigmentation in hypertrophic scarring after burns.Conclusions: Further studies with more samples to determine the substances contained in aloe vera that can accelerate changes in consistency, pigmentation, and height.